Analysis of the Role of Community Participation in the Successful Implementation of the City without Slums (Kotaku) Program in Rambung Village in Binjai District South of Binjai City - Al’Amin, Muhammad Nurul; Badaruddin, Badaruddin; Tarmizi, H. B. (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This research focuses on field research and the methods used in this study are descriptive of qualitative and quantitative analysis. The data was mainly obtained from respondents with purposive sampling techniques, based on questionnaires and interview results as primary data, while also equipped with secondary data. The results of the research study showed that the policy of drafting a general spatial plan of Pati City in practice turned out to be some differences with normative. The form of community participation is dominated by the form of input / suggestion / proposal and donation of information / data. It can be concluded that the method of community participation in the activities of Kota Without Slums (Kotaku) in Rambung Dalam Village, is an obligation that must be implemented by the government, because of the demands of decentralization in regional autonomy that wants the government to play a role with other stakeholders in development planning. While the goal of community empowerment that wants to be achieved with participation itself has not been realized. So that the goals of development programs involving community participation can be achieved and the resulting planning activities can be used fully as a reference in development, it is necessary to apply the principle of transparency at every stage and improvements are made to the process of implementing government policies, as the ideal concept applies normatively.